2013
DOI: 10.1016/j.resp.2013.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Activation of inspiratory muscles via spinal cord stimulation

Abstract: Diaphragm pacing is a clinically useful modality providing artificial ventilatory support in patients with ventilator dependent spinal cord injury. Since this technique is successful in providing full-time ventilatory support in only ~50% of patients, better methods are needed. In this paper, we review a novel method of inspiratory muscle activation involving the application of electrical stimulation applied to the ventral surface of the upper thoracic spinal cord at high stimulus frequencies (300 Hz). In an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 91 publications
0
24
0
Order By: Relevance
“…If similar to HF-SCS of the upper thoracic spinal cord, which causes in activation of the inspiratory muscles, this method described herein causes activation of expiratory motoneurons rather than motor roots (DiMarco and Kowalski, 2009, 2013). Whether expiratory motoneurons are activated directly or via a spinal network is uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If similar to HF-SCS of the upper thoracic spinal cord, which causes in activation of the inspiratory muscles, this method described herein causes activation of expiratory motoneurons rather than motor roots (DiMarco and Kowalski, 2009, 2013). Whether expiratory motoneurons are activated directly or via a spinal network is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…In prior studies utilizing HF-SCS applied to the upper thoracic SCS to activate the inspiratory muscles, we demonstrated that electrical stimulation with stimulus frequencies in the range of ~300 Hz with low currents (~1–2 mA) results in very large inspired volumes approximating the inspiratory capacity (DiMarco and Kowalski, 2009, 2013). Our results suggested that upper thoracic HF-SCS results in activation of the phrenic and intercostal motoneuron pools allowing processing of the signal, and the activation of the inspiratory muscles at physiological firing frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of kilohertz frequency (1–10 KHz ) spinal cord stimulation (kHz-SCS) 17 for the treatment of neuropathic pain has engendered studies on new mechanisms of actions (MoA) 5,811 . Divergent clinical observations for conventional rate SCS and kHZ-SCS suggest difference in MoA which could in turn inform distinct programming optimization strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Various management regimes and interventions for respiratory impairment have been documented in the literature, including direct and indirect targeting of respiratory muscle strength and endurance, and interventions through environmental adaptations (mechanical ventilation, pacing of the phrenic nerve or diaphragm ± intercostal muscles, abdominal binders, pharmaceuticals, e.g. theophylline and baclofen) [20,[25][26][27][28][29][30][31][32][33][34][35][36]. In general, the outlook appears positive for some degree of functional respiratory improvement, with flow-on effects to verbal communication and related areas of activity and participation, given continued collaboration between multiple disciplines (e.g.…”
Section: Sci Core Setsmentioning
confidence: 99%